REALIZING AN INDEPENDENT VILLAGE: THE ROLE OF LOCAL LEADERS IN IMPROVING THE QUALITY OF DEVELOPMENT PLANNING - Ginting, Arwanto Harimas; Wahyuningsih, Dewi Rahmi (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2024)
Development planning is to prepare a development plan that serves as a guide or reference. Regional governments carry out the development based on the capabilities and potential of resources (natural and human) as well as existing economic opportunities. Thus, the development planning can be realized. Local leaders, particularly Village Heads, play a crucial role as they engage directly with the community, possessing authority given by the regent, mayor, or district head. This research used qualitative research methods with a descriptive approach. The results of this research indicate that the role of the Village Head in administering the government of the development planning process in Limpung Village is generally going quite well, although the results have not yet reached optimal outcomes. Optimizing the role of the village head is crucial so that the unexecuted development can be completed in accordance with the plannings and objectives.Keywords: Role, Local Leaders, Development Planning